Representasi Nilai Sufistik dalam Puisi “Tarjumān al-‘Asywāq” dan Puisi “Perjalanan ke Langit” - Alfain, Bihevi; Tasnimah, Tatik Mariyatut; Kumalasari, Kumalasari (Universitas Al Azhar Indonesia, 2025)
Poetry serves as a medium to express the profound relationship between humans and God through mystical traditions. “Tarjumān al-‘Asywāq” by Ibnu Arabi and “Perjalanan ke Langit” by Kuntowijoyo represent the spiritual journey of a servant towards God, a spiritual journey that is full of sufistic values. This research aims to reveal the thoughts of Ibnu Arabi and Kuntowijoyo in the sufistic concept and to reveal the sufistic value of the poem “Tarjumān al-‘Asywāq” by Ibnu Arabi and the poem “Perjalanan ke Langit” by Kuntowijoyo. This research is a comparative research because it compares the sufistic values in the poem “Tarjumān al-‘Asywāq” by Ibnu Arabi and the poem “Perjalanan ke Langit” by Kuntowijoyo. Data collection techniques involving observation and note-taking. The data analysis is comparative analysis and uses a sufism approach. The poem “Tarjumān al-‘Asywāq” is a classical poem using Arabic and the poem “Perjalanan ke langit” is a modern poem using Indonesian. Despite their differences background, languages, countries, and eras, both poems affirm that the spiritual journey can transcend geographical and cultural boundaries, both poems convey universal messages about the search for divine meaning and and the relationship between humans and God.Keywords – Arabic Poetry, Indonesian Poetry, Mysticism, Sufi Values.